Physical rehabilitation of the visually impaired and its implications for tactile modelling - Srivastava, Namrata; Pachauria, Poonam; Nitesh (International Journal Of Community Medicine And Public Health, 2024)
The aim of this study is to investigate the effect of tactile models in improving the health of visually impaired people. The main objective of the intervention is to improve mobility, muscle strength, flexibility and physical fitness. Longitudinal study, this study was approved by the research ethics committee “Naraina Medical College and Research Centre (NMCRC)” Kanpur, Uttar Pradesh. Convenience sampling was conducted over a three-week period from December 2021 to January 2022. The physical rehabilitation of the visually impaired (PP-PVI) process includes physical assessment, language selection, design structure and visually impaired language. A longitudinal study was conducted with youth and young adults with visual impairment. They received treatment twice a week for 12 months and their quality of life was assessed before and after treatment. Quality of life was assessed using the 30-item short form health questionnaire (SF-30). Mean scores improved in all domains except the quality of life questionnaire after PP-PVI. PP-PVI has proven to be a valuable, easy-to-understand, and reliable clinical tool. This product is for people with visual impairment. Implications for Professionals: PP-PVI exercise improves many aspects of your body and performance. This plays an important role in ensuring independence for people with low vision. Physical therapy is effective in improving visual and tactile motor skills. Physical therapists can help improve the overall function and quality of life of people with these problems through targeted exercises and activities.